ANALISA MANFAAT PEMBIAYAAN GADAI EMAS SYARIAH: STUDI KASUS BANK SYARIAH MANDIRI-TOMANG RAYA - Natasha Putri Bahari; Lucky Nugroho; Ahmad Badawi; Nurul Hidayah (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2021)
One of the superior products that distinguish between Islamic banks and conventional banks is Rahn or a pawn. However, these products are not owned by all Islamic banks. Furthermore, one of the sharia banks that have gold Rahn products or sharia gold pawn financing is Bank Syariah Mandiri (BSM), where BSM is also the largest Islamic bank with assets in Indonesia. This study aims to analyze the use of Islamic bank gold pawn financing for the community. The method used is a qualitative descriptive method with primary data. The sample used is customers of the BSM Tomang Raya Branch who have gold pawn financing facilities, amounting to 30 customers. The research questions are (i) What are the characteristics of the customers of sharia gold pawn financing;(ii) How is the use of Islamic gold pawn financing. The results of the research show that the majority of the age range of customers for sharia gold pawn financing is productive age (30-49 years), the majority of the sexes are women, the occupation of the majority of customers is private employees, the majority of customers› income is> IDR 5,000,000 per month. , the majority of customer education is S-1 and the religion of the majority of customers is Muslim. In addition, the use of borrowed money from sharia gold pawn financing is intended for consumer needs.